2023
DOI: 10.3390/cells12060905
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Progress toward Unlocking the Power of Epigenetics in NSCLC: Latest Updates and Perspectives

Abstract: Epigenetic research has the potential to improve our understanding of the pathogenesis of cancer, specifically non-small-cell lung cancer, and support our efforts to personalize the management of the disease. Epigenetic alterations are expected to have relevance for early detection, diagnosis, outcome prediction, and tumor response to therapy. Additionally, epi-drugs as therapeutic modalities may lead to the recovery of genes delaying tumor growth, thus increasing survival rates, and may be effective against t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 167 publications
0
1
0
Order By: Relevance
“…Previous studies have reported various serum miRNA signatures for NSCLC diagnosis, prognosis, and response to therapy. However, most of these studies used small sample sizes, different platforms, or different normalization methods, which may limit the reproducibility and comparability of the results [13,[30][31][32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported various serum miRNA signatures for NSCLC diagnosis, prognosis, and response to therapy. However, most of these studies used small sample sizes, different platforms, or different normalization methods, which may limit the reproducibility and comparability of the results [13,[30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Circulating cell-free miRNAs (cf-miRNAs) have several advantages as diagnostic biomarkers for NSCLC, including stability, abundance, and specificity. Furthermore, cf-miRNAs can predict drug response by monitoring genetic profiles during treatment, presenting significant potential for personalized therapy [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Using advanced methods to explore new genetic and epigenetic markers represents a significant step forward in distinguishing between squamous cell carcinoma (SCC) and adenocarcinoma (ADC) compared to traditional examination methods [1,2]. While histopathology is considered the gold standard, it faces challenges such as inconsistent results from immunohistochemical staining (IHC), variations in tumor characteristics, and difficulties in interpreting staining results [2].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to genetic mutations, epigenetic modifications play a crucial role in NSCLC development and progression. The epigenetic landscape of NSCLC is characterized by various alterations, including DNA methylation, histone modifications, and non-coding RNA expression [2,3]. These changes can affect the expression of key protein-coding genes involved in cellular processes such as cell cycle regulation, apoptosis, invasion, metastasis, angiogenesis, immune response, and drug resistance [3].…”
Section: Introductionmentioning
confidence: 99%
“…The epigenetic landscape of NSCLC is characterized by various alterations, including DNA methylation, histone modifications, and non-coding RNA expression [2,3]. These changes can affect the expression of key protein-coding genes involved in cellular processes such as cell cycle regulation, apoptosis, invasion, metastasis, angiogenesis, immune response, and drug resistance [3]. Epigenetic alterations can also interact with genetic mutations and modulate their effects on tumor phenotype and behavior [3].…”
Section: Introductionmentioning
confidence: 99%